Ground- and excited-state properties of Re(I) carbonyl complexes – Effect of triimine ligand core and appended heteroaromatic groups. (August 2021) - Choroba, Katarzyna; Kotowicz, Sonia; Maroń, Anna; Świtlicka, Anna; Szłapa-Kula, Agata; Siwy, Mariola; Grzelak, Justyna; Sulowska, Karolina; Maćkowski, Sebastian; Schab-Balcerzak, Ewa; Machura, Barbara
Abstract: In this work, a series of six rhenium(I) complexes bearing 2, 2′:6′, 2″-terpyridine ( terpy ), 2, 6-di(thiazol-2-yl)pyridine ( dtpy ), and 2, 6-di(pyrazin-2-yl)pyridine ( dppy ) with appended quinolin-2-yl and N-ethylcarbazol-3-yl groups were prepared and spectroscopically investigated to evaluate the photophysical consequences of both the trisheterocyclic core ( terpy, dtpy and dppy ) and the heterocyclic substituent. The [ReCl(CO)3 (L n -κ 2 N)] complexes are regarded as ideal candidates for getting structure–property relationships, while terpy -like framework represents an excellent structural backbone for structural modifications. The replacement of the peripheral pyridine rings of 2, 2′:6′, 2″-terpyridine by thiazoles and pyrazines resulted in a significant red-shift of the absorption and emission of [ReCl(CO)3 (L n -κ 2 N)] due to stabilization of the ligand-centred LUMO orbital. Both quinoline and N-ethylcarbazole are extended π-conjugation organic chromophores, but they differ in electron-donating abilities. The low-energy absorption band of Re(I) complexes with the triimine ligands bearing quinolin-2-yl group was contributed by the metal-to-ligand charge-transfer (MLCT) electronic transitions. The introduction of electron-donating N-ethylcarbazol-3-yl substituent into the triimine acceptor core resulted in the change of the character of the HOMO of Re(I) complexes and a significant increase of molar absorption coefficients of the long-wavelength absorption, which was assigned to a combination of 1 MLCT and 1 ILCT (intraligand charge-transfer) transitions. Regardless of the appended heteroaromatic group, the emitting excited state of Re(I) terpy -based complexes was demonstrated to have predominant 3 MLCT character, as evidenced by comprehensive studies including static and time-resolved emission spectroscopy along with ultrafast transient absorption measurements. The diodes with Re(I) complexes dispersed molecularly in a PVK:PBD matrix were emissive and effects of the complex structure on colour of emitted light and its intensity was pronounced. Highlights: A series of Re(I) complexes with terpy-like ligands was prepared. Impact of the ligand architecture on the photophysical properties was investigated. The character of the emitting excited state was determined. The capacity of obtained compounds for electroluminescence was primarily tested.